PENGARUH PROFESIONALISME APARAT KELURAHAN TERHADAP KUALITAS PELAYANAN PUBLIK DI KELURAHAN MALALAYANG SATU KECAMATAN MALALAYANG KOTA MANADO - Mandey, Donevan Jeremy; Mandey, Jantje; Tulusan, Femmy (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: Improving the quality of public services required of civil servants who are not only in termsof quantity, but also requires the ability professionalism and moral qualities are directly proportionalto the demands of society. Human resource development within the ranks of government (publicorganizations) need to be directed at upgrading professional skills and the development of professionalethics which is accompanied by a spirit of service to the public (community). For the purpose of thisstudy to analyze the influence of professionalism village government officials on the quality of publicservices in the Village Malalayang One Malalayang District of Manado City.This research method using diagnostic analytic design with descriptive-quantitative method andexplanatories survey. The use of quantitative methods and explanatory descriptive-survey possiblebecause this study raised the issue of considerable actual and aims to analyze social phenomena andexamine the relationship between the phenomenon or effect. The population in this study were allvillage officials and community service users in villages Malalayang One Malalayang District ofManado City. The purposive sampling conducted as many as 30 people, consisting of 15 peopleMalalayang The village government apparatus and the remaining 15 persons from the community ofusers of services.the results of this study shows there is a strong indication that when village officials increasedprofessionalism (high) will encourage the improvement of the quality of public services. These resultsare consistent with the results of a simple linear regression analysis to the equation Y = 2.062 + 1.040X,and product moment correlation coefficient r of 0.809.Keyword : Profesionalism, Publik Service Quality